Distribution of Scientific paper from Sulawesi Island State Universities on Social Media Using an Almetric Approach - Awalya, Misrha Tul; Ibrahim, Cecep; Jaya, Asrul; Masrul, Masrul (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Altmetric is metrics and data information to measure the interaction of scientific paper on social media through the data obtained. This study examines the distribution of scientific papers of Sulawesi island state universities on social media. This study uses a quantitative descriptive. The stages of this research consist of problem identification, data collection, data pre-processing, altmetrics approach analysis and discussion results. This research was conducted online by taking data in the form of scientific paper citation data including keywords affiliated with the Sulawesi Island state university and the year being limited from 2020-2022, while social media data was obtained from Altmetrics.com by extracting DOIs from every scientific publication on Scopus. com. The social media that are the focus of this research are Twitter, Facebook, Blog, and Mendeley. The results of this research show that the distribution of scientific papers of state universities on the island of Sulawesi on social media is Mendeley with a total of 15,378 Readers, Twitter with 3,124 Mentions, Blogs with 77 Posted and Facebook with 30 Shared. These results show that apart from being popular on academic platforms or international journals (Scopus), the public universities on the island of Sulawesi are also popular on Mendeley's social media platforms, Twitter, Blogs, Facebook..